تأصيل الإمام الشافعي لحجية السّنة النبوية وثبوتها دراسة في ملامح النظرية الأصولية - نجم الدين قادر الزنكي (International Institute of Islamic Thought, 2010)
تبحث الدراسة معالم السنة عند الشافعي سالكةً منهجاً وصفياً تحليلياً. وخلُصَتْ إلى أن السنة عند الشافعي دليل يتكامل مع القرآن ولا يتناسخان؛ لأن تبادل النسخ بينهما خارم لاستقلالهما ومخلٌّ بوظيفتهما التشريعية المتميزة. لذا ينبغي أن يبقيا متكاملين متزاوجين لا يغادر بعضهما بعضاً البتة، ولا ينفصلان عن بعضٍ بحال. This study defines the milestones of Sunnah from Imam Shafi'i's perspective. The methodology used is a descriptive analytical one. According to Shafi'i, the Qur'an and Sunnah are two complementing sources. They should not abrogate each other, because this abrogation contradicts the independent authority of each one and runs against the complementary relationship regulating their unique functions. Therefore, they are two integrated sources which can never separate nor can divorce one another.